The study of digital literacy components for youths during the COVID-19 pandemic in Bangkok, Thailand - Ruthairat Siriwattanarat; Weerawich Wongroj; Kittikhun Meethongjan; Donsak Tsailexthim (Institute of Advanced Engineering and Science, 2024)
This research paper investigates digital literacy components for youths in Bangkok. The first phase used a qualitative method. The key informants were eight experts in information and communication technology (ICT), human resource (HR), and education. The second phase was to develop the measurement of digital literacy components using the confirmatory factor analysis (CFA) approach with a sample consisting of 1,362 youths in Bangkok. Data collection was conducted through a questionnaire with 52 questions. The results revealed that digital literacy criteria for youths in Bangkok consisted of four factors containing 13 indicators. The first factor and its related access components was three subcomponents, which are i) use of tools and devices; ii) data collection in the cloud; and iii) internet connection. The second factor was understanding components consisting of evaluation, ethics, and legal literacy. The third factor was use of components consisting of safeguarding, search, sharing, and innovation. The fourth factor was creating components consisting of creating weblogs/applications, presenting on website/application, and safeguarding. CFA was employed to test the construct validity of the research latent variables that revealed the harmony correlation of empirical data contained in this research model. These results were employed to develop a digital literacy for youth during the COVID-19 pandemic in Bangkok, Thailand.